Sikap dan motivasi murid Iban dalam mempelajari bahasa melayu sebagai bahasa kedua - Jerie Anak Peter Langan,; Zamri Mahamod, (Penerbit UKM, 2011)
The aim of this study is to identify the attitude and motivation among Iban pupils in primary school in the learning of Malay Language as a second language. This study tries to identify the existance of differences in attitude and motivation between the two genders of Iban pupils in the learning Malay Language. 302 year 6 Iban pupils from 15 schools in the Kanowit district were selected as respondents using the purposeful sampling method. This study was carried out using the Gardner Socio-Educational Model. Questionnaire consisting of 36 items was distrubet to collect data for this study. These items were divided into attitude and motivation contructs. The data were analyzed by using descriptive and inferential statistics. The result of the study shows that Iban pupils in the primary schools have positive attitude and high motivation level in the learning of Malay Language as a second language. However, the level of motivation is low when they have to spend more time to study the Malay Language as compared to other subjects. This study also reveals the significant differences in motivation level between male and female pupils in the learning of Malay Language. The conclusion is Iban pupils have positive attitude and high motivation level while studing Malay Language inside or outside the classroom